Rotation of cell surface and dissolved biomolecules examined by fluorescence imaging, time-tagged single-photon counting, and fluorescence depletion anisotropy - Pace, Jason M., author; Barisas, B. George, advisor; Crans, Debbie C., committee member; Roess, Deborah A., committee member; Van Orden, Alan K., committee member (Colorado State University. Libraries, 2022)
In this dissertation, I discuss our studies examining protein rotation both in solution and on single cells. Chapter I gives background on physics of rotational diffusion, the application of these measurements to cellular systems, and a general overview of the field, including a survey of techniques that have been used to measure rotation of membrane proteins. In the next two chapters, I discuss our research on the effect of various cell treatments known to perturb the dynamics of membrane proteins on the rotation of the high-affinity Type I IgE receptor (FcεRI) expressed on RBL-2H3 cells. I investigated effects on receptor rotation resulting from treatment with IgE antibody as well as from four treatments with IgE and an additional agent including DNP-BSA, paraformaldehyde, MβCD, and cytochalasin D. These agents have varied effects that I expect to cause a significant perturbation of the rotational dynamics of the receptor. These effects range from receptor crosslinking by DNP-BSA and paraformaldehyde which would be expected to hinder receptor rotation to effects on membrane cholesterol content and the underlying cytoskeleton in the cases of MβCD and cytochalasin D, the effects of which are more uncertain and thus of particular interest. I have investigated these phenomena using a single-particle fluorescence imaging approach and, alternatively, a time-tagged single photon counting approach. These topics are the subject of Chapters II and III respectively. These two approaches, while both designed with the intent to investigate the rotational dynamics of membrane proteins using fluorescence microscopy, share little in common with regards to their methods of data collection and analysis. The concepts behind them are completely different and they use an entirely different set of analysis programs. Chapter IV consists of a published manuscript entitled "Continuous fluorescence depletion anisotropy measurement of protein rotation" which describes our work using a newly-developed pump-probe technique to examine protein rotation in solution and extends this to single-cell measurements. In the continuous variant of fluorescence depletion anisotropy used here, the intensity and polarization of a laser beam are modulated continuously by a programmed acousto-optic modulator and Pockels cell respectively to produce the desired excitation waveform. We have used this method to examine rotation of eosin conjugates of carbonic anhydrase, BSA, and immunoglobulin G in 90% glycerol at varying temperatures. We have also explored the potential application of this method to single-cell measurements and recorded preliminary results on eosin-IgE-bound FcεRI. Generally, we found good agreement with time-resolved phosphorescence anisotropy measurements of rotation of solution-phase molecules and of cell surface FcεRI. Chapter V discusses future avenues worth exploring which would improve upon the methods presented in Chapters II and III. These include faster cameras to access shorter timescales, gold nanorods to improve the signal-to-noise ratio, and a method to obtain a true anisotropy in a microscope.
Keywords: fluorescence correlation spectroscopy; rotational diffusion; Type I Fcepsilon receptor; polarized fluorescence depletion; continuous fluorescence depletion anisotropy; time-tagged single-photon counting